Prospects of Metal‐Free Perovskites for Piezoelectric Applications. Issue 12 (24th February 2022) - Wu, Han‐Song; Murti, Bayu Tri; Singh, Jitendra; Yang, Po‐Kang; Tsai, Meng‐Lin
Abstract: Metal‐halide perovskites have emerged as versatile materials for various electronic and optoelectronic devices such as diodes, solar cells, photodetectors, and sensors due to their interesting properties of high absorption coefficient in the visible regime, tunable bandgap, and high power conversion efficiency. Recently, metal‐free organic perovskites have also emerged as a particular class of perovskites materials for piezoelectric applications. This broadens the chemical variety of perovskite structures with good mechanical adaptability, light‐weight, and low‐cost processability. Despite these achievements, the fundamental understanding of the underlying phenomenon of piezoelectricity in metal‐free perovskites is still lacking. Therefore, this perspective emphasizes the overview of piezoelectric properties of metal‐halide, metal‐free perovskites, and their recent progress which may encourage material designs to enhance their applicability towards practical applications. Finally, challenges and outlooks of piezoelectric metal‐free perovskites are highlighted for their future developments. Abstract : In this perspective, the authors summarize the structures and origin of non‐centrosymmetric orientation of metal‐free perovskites. They further discuss the mechanisms including symmetry breaking, external stimulus, and morphotropic phase boundary commonly observed in piezoelectric devices. Finally, they propose possible applications of metal‐free perovskites such as piezoelectric sensors, actuators, nanogenerators, and piezotronic devices.